Improved inhibition of telomerase by short twisted intercalating nucleic acids under molecular crowding conditions - Agarwal, Tani; Pradhan, Devranjan; Geci, Imrich; El-Madani, Amro M.; Petersen, Michael; Pedersen, Erik B.; Maiti, Souvik (Nucleic Acid Therapeutics, 2012)
Human telomeric DNA has the ability to fold into a 4-stranded G-quadruplex structure. Several G-quadruplex ligands are known to stabilize the structure and thereby inhibit telomerase activity. Such ligands have demonstrated efficient telomerase inhibition in dilute conditions, but under molecular crowding conditions mimicking physiological milieu, stabilization of the telomeric G-quadruplex is often lost. We attempted to demonstrate the enhanced G-quadruplex stabilizing ability under molecular conditions by using twisted intercalating nucleic acids (TINA)-modified oligonucleotides. We have shown using circular dichroism and ultraviolet spectroscopic methods that these TINA-modified short oligonucleotides function as G-quadruplex, inducing agents and participate in the formation of stabilized 3:1 G-quadruplex with the human telomeric oligonucleotide. Using enzyme-linked immunosorbent assay-based telomerase repeat amplification assay (TRAP) assay as well as nondenaturing polyacrylamide gel electrophoresis-based TRAP, we demonstrate remarkable enhancement in their anti-telomerase activity even under molecular crowding conditions. This is the first time in which a G-quadruplex stabilizing agent has demonstrated enhanced activity even under molecular crowding conditions.